Determination of Heat Conductivity Coefficient of a Cable Bundle by Inverse - Čiegis, R.; Meilūnas, M.; Jankevičiūtė, G.; Ilgevičius, A. (Elektronika ir Elektrotechnika, 2009)
The aim is to identify thoroughly the mixed heat conduction coefficients k0 of the cable bundles using the inverse problem solution method. Determination of the heat conductivity coefficients of an electrical cable bundle is one of the main problems when simulating the heat transfer of such a problem. The so-called “mixed” conductivity coefficient of the wire isolation material (e.g. polyvinyl chloride (PVC)) and air is replaced by the heat conduction in PVC with the smaller conduction value. The proposed evaluation procedure of the parameter k0, is applied to generalize the mathematical model [1] of the heat transfer in a cable bundle (up to 40 single wires) for passenger vehicles. From the fitted results a very good agreement with the measurements can be seen. Ill. 1, bibl. 8 (in English; summaries in English, Russian and Lithuanian).